Anthocyanin extraction from roselle (Hibiscus sabdariffa L.) calyces: A microwave-assisted approach using Box-Behnken design - Intan Dewi Larasati; Ceferino Carrera; Hanifah Nuryani Lioe; Teti Estiasih; Nancy Dewi Yuliana; Manikharda; Hamidie Ronald Daniel Ray; Miguel Palma; Widiastuti Setyaningsih (Journal of Agriculture and Food Research, 2024)
Roselle (Hibiscus sabdariffa L.) is a widely consumed edible flower, often utilized as a natural coloring agent. The bright red color of roselle is due to its anthocyanin content. Beyond their role as colorants, anthocyanins are known for their potent antioxidant properties, which have drawn significant interest for their potential health benefits. To fully harness the advantages of roselle's anthocyanins, developing a reliable extraction method is crucial. This study aimed to establish a fast, efficient, and environmentally friendly extraction technique using microwave-assisted extraction (MAE). Key factors, such as temperature (30, 65, and 100 °C), solvent concentration (30 %, 50 %, and 70 % ethanol in water), and solvent-to-solid ratio (10:1, 25:1, 40:1), were optimized using the Box-Behnken design combined with response surface methodology. The extraction time (5–30 min) was also evaluated to maximize anthocyanin recovery. Two major anthocyanins, delphinidin-3-sambubioside and cyanidin-3-sambubioside, were identified using UHPLC-PDA-QToF-MS and quantified using a cyanidin-3-glucoside calibration curve. The optimal extraction conditions were found to be 72 °C, using 70 % ethanol in water with a 40:1 solvent-to-solid ratio for 15 min. This method was validated with high accuracy (>98 % recovery) and precision (CV <6 %). It was successfully applied to quantify the anthocyanin content in both purple and red roselle varieties. This rapid and effective MAE method offers a more sustainable, energy-efficient, and time-saving alternative to conventional extraction methods, benefiting industries that rely on natural colorants and antioxidants.